Psychological impact of COVID-19: Assessing the COVID-19-related anxiety, individual’s resilience and conspiracy beliefs on attitudes to COVID-19 vaccination - Rosli, Nadzirah; Johar, Elaina Rose; Rosli, Nursyafinaz; Abdul Hamid, Nor Fazilah (Frontiers in Psychology, 2022)
It has been two years since the first outbreak of the COVID-19 virus, and continuous efforts and measures have been exerted and implemented to halt its spread, such as the introduction of vaccination programs. However, as with the consumption of other products and services, some people hold different beliefs, consequently affecting their attitudes towards COVID-19 vaccination. Thus, vaccine unwillingness and hesitancy remain an enormous concern for many countries. This paper explores the effects of anxiety, individual’s resilience, and conspiracy beliefs on attitudes towards COVID-19 vaccines among the population of Malaysia – with a focus on Muslim individuals. We used survey data from 438 respondents (205 male, 233 female) to assess the research model. To conduct the multi-group analysis, we used partial least square structural equation modelling in SmartPLS 3. The results suggest that anxiety is positively associated with COVID-19 vaccination attitudes, whereas conspiracy beliefs have an inverse effect on vaccination attitudes, while individual’s resilience is also positively associated with vaccination attitudes. Furthermore, it is found that the relationship between conspiracy beliefs and vaccination attitudes is weakened for individual with higher level of resilience. The findings also reveal the differences and similarities between males and females. To the best of our knowledge, this study is the first to simultaneously explore and demonstrate the effects of COVID-19-related anxiety, conspiracy beliefs and resilience with people's attitudes towards COVID-19 vaccines and to examine the homogeneity of both males and females – especially among Malaysia’s Muslim population – thereby offering a valuable contribution to the literature.